2013
DOI: 10.1088/0004-637x/764/1/77
|View full text |Cite
|
Sign up to set email alerts
|

The Detection of C60 in the Well-Characterized Planetary Nebula M1-11

Abstract: We performed multiwavelength observations of the young planetary nebula (PN) M1-11 and obtained its elemental abundances, dust mass, and the evolutionary status of the central star. The AKARI/IRC, VLT/VISIR, and Spitzer/IRS spectra show features due to carbon-rich dust, such as the 3.3, 8.6, and 11.3 μm features due to polycyclic aromatic hydrocarbons (PAHs), a smooth continuum attributable to amorphous carbon, and the broad 11.5 and 30 μm features often ascribed to SiC and MgS, respectively. We also report th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 87 publications
(161 reference statements)
1
44
0
Order By: Relevance
“…Long after the initial proposed identification of C + 60 in the ISM by Foing & Ehrenfreud (1994) taking advantage of the laboratory spectrum of Fulara et al (1993a), the presence of C 60 + has been recently confirmed in diffuse interstellar clouds and the presence of C 60 previously in various environments as described by Cami (2014) and Berné et al (2015b), among others: various types of carbon-rich planetary nebulae (Cami et al 2010;García-Hernández et al 2010, 2011aGielen et al 2011, Otsuka et al 2013); a single pre-planetary nebula (Zhang & Kwok 2011); various interstellar environments (Rubin et al 2011;Peeters et al 2012;Boersma et al 2012), including reflection nebulae such as NGC 7023 (Sellgren et al 2007(Sellgren et al , 2010Berné & Tielens 2012) and young stellar objects (Roberts et al 2012).…”
Section: Interstellar Abundancesmentioning
confidence: 97%
“…Long after the initial proposed identification of C + 60 in the ISM by Foing & Ehrenfreud (1994) taking advantage of the laboratory spectrum of Fulara et al (1993a), the presence of C 60 + has been recently confirmed in diffuse interstellar clouds and the presence of C 60 previously in various environments as described by Cami (2014) and Berné et al (2015b), among others: various types of carbon-rich planetary nebulae (Cami et al 2010;García-Hernández et al 2010, 2011aGielen et al 2011, Otsuka et al 2013); a single pre-planetary nebula (Zhang & Kwok 2011); various interstellar environments (Rubin et al 2011;Peeters et al 2012;Boersma et al 2012), including reflection nebulae such as NGC 7023 (Sellgren et al 2007(Sellgren et al , 2010Berné & Tielens 2012) and young stellar objects (Roberts et al 2012).…”
Section: Interstellar Abundancesmentioning
confidence: 97%
“…Furthermore, in addition to other species, SiO and SO 2 have been recently identified toward the middle-aged PN M2-48 . Perhaps even more remarkable has been the recent discovery of C 60 in a few planetary nebulae (e.g., Cami et al 2010;García-Hernández et al 2010Otsuka et al 2013). Clearly, the molecular portfolio of planetary nebulae continues to grow.…”
Section: Introductionmentioning
confidence: 99%
“…We refer to the results by Georgiev (2009) for IC418 andOtsuka et al (2013) for M1-11. Since there is no information on gas emission line fluxes, except for Hβ, the effective temperature T eff , and the distance d, we could not model Hen2-68 and K3-62 using Cloudy.…”
Section: Properties Of the Central Stars And The Nebulaementioning
confidence: 99%
“…However, the first confirmed detection of cosmic fullerenes was only recently reported by Cami et al (2010) in the C-rich planetary nebula (PN) Tc1. Since then, a plethora of papers reported the discovery of cosmic fullerenes in Galactic (García-Hernández et al 2010Otsuka et al 2013;Zhang & Kwok 2011) and Large/Small Magellanic PNe ⋆ E-mail:otsuka@asiaa.sinica.edu.tw (García-Hernández et al 2010, Galactic asymptotic giant branch (AGB) stars ), H-poor R Coronae Borealis (R CrB) stars (García-Hernández et al 2011b;Clayton et al 2011), reflection nebulae (Sellgren et al 2010;Peeters et al 2012), a binary XX Oph star (Evans et al 2012), and YSOs (Roberts et al 2012). While the number of fullerene detections is increasing, the formation process and the excitation mechanism of fullerenes in evolved stars are the subject of active research.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation